2022
DOI: 10.3390/plants11131684
|View full text |Cite
|
Sign up to set email alerts
|

Root-Zone Heat Priming Effects on Maximum Quantum Efficiency of PSII, Productivity, Root Morphology and Nutritional Quality of Two Aeroponically Grown Leafy Greens in a Tropical Greenhouse

Abstract: This study investigated the effects of root zone (RZ) heat priming on Eruca sativa (cv. Arugula) and Lactuca sativa (cv. Canasta) in a tropical greenhouse by exposing them to three different RZ temperatures (RZTs). For the first group, plants were grown at 25 °C-RZT for 36 days. The second group of plants was grown at 25 °C-RZT for 10 days before transferring to 38 °C-RZT for 10 days and then to 42 °C-RZT for another 16 days (primed). For the third group, plants were grown at 25 °C-RZT for 20 days and for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In another recent study, we carried out the same RZ heat priming for 10 days for the same species in the same greenhouse, but plants were exposed to a subsequent RZT of 42 • C for 16 days. It was found that RZ heat priming at RZT of 38 • C resulted in the slower leaf expansion of canasta after six days of RZ heat priming compared to those grown under RZT of 25 • C. However, RZ heat priming did not affect the leaf expansion of arugula compared to 25 • C-RZT plants [20]. During RZ heat priming, dynamic photoinhibition measured by lowered midday Fv/Fm ratios in canasta leaves [20] could lead to a decline in overall photosynthetic performance [17,86], which could be partially responsible for the slower leaf growth.…”
Section: Root-zone (Rz) Heat Priming Effects On Growth Productivity P...mentioning
confidence: 93%
See 4 more Smart Citations
“…In another recent study, we carried out the same RZ heat priming for 10 days for the same species in the same greenhouse, but plants were exposed to a subsequent RZT of 42 • C for 16 days. It was found that RZ heat priming at RZT of 38 • C resulted in the slower leaf expansion of canasta after six days of RZ heat priming compared to those grown under RZT of 25 • C. However, RZ heat priming did not affect the leaf expansion of arugula compared to 25 • C-RZT plants [20]. During RZ heat priming, dynamic photoinhibition measured by lowered midday Fv/Fm ratios in canasta leaves [20] could lead to a decline in overall photosynthetic performance [17,86], which could be partially responsible for the slower leaf growth.…”
Section: Root-zone (Rz) Heat Priming Effects On Growth Productivity P...mentioning
confidence: 93%
“…It was found that RZ heat priming at RZT of 38 • C resulted in the slower leaf expansion of canasta after six days of RZ heat priming compared to those grown under RZT of 25 • C. However, RZ heat priming did not affect the leaf expansion of arugula compared to 25 • C-RZT plants [20]. During RZ heat priming, dynamic photoinhibition measured by lowered midday Fv/Fm ratios in canasta leaves [20] could lead to a decline in overall photosynthetic performance [17,86], which could be partially responsible for the slower leaf growth. Improvements in heat resistance to prevent damage to the photosynthetic apparatus may be coupled with reduced photosynthetic performance during heat priming.…”
Section: Root-zone (Rz) Heat Priming Effects On Growth Productivity P...mentioning
confidence: 93%
See 3 more Smart Citations